Blockchain-based healthcare management system with two-side verifiability - Tan, Tian Lim; Salam, Iftekhar; Singh, Madhusudan (PloS one, 2022)
The lack of data outsourcing in healthcare management systems slows down the intercommunication and information sharing between different entities. A standard solution is outsourcing the electronic health record (EHR) to a cloud service provider (CSP). The outsourcing of the EHR should be performed securely without compromising the CSP functionalities. Searchable encryption would be a viable approach to ensure the confidentiality of the data without compromising searchability and accessibility. However, most existing searchable encryption solutions use centralised architecture. These systems have trust issues as not all the CSPs are fully trusted or honest. To address these problems, we explore blockchain technology with smart contract applications to construct a decentralised system with auditable yet immutable data storage and access. First, we propose a blockchain-based searchable encryption scheme for EHR storage and updates in a decentralised fashion. The proposed scheme supports confidentiality of the outsourced EHR, keyword search functionalities, verifiability of the user and the server, storage immutability, and dynamic updates of EHRs. Next, we implement a prototype using JavaScript and Solidity on the Ethereum platform to demonstrate the practicality of the proposed solution. Finally, we compare the performance and security of the proposed scheme against existing solutions. The result indicates that the proposed scheme is practical while providing the desired security features and functional requirements.